Live vaccines—a short‐cut to cancer viro‐immunotherapy. Issue 1 (20th November 2019) - Wirth, Thomas C; Niemann, Julia; Kühnel, Florian
Abstract : Tumour immunotherapies have been a breakthrough in clinical oncology but only a few patients benefit from this progress. Additional interventions that sensitize immunologically cold tumours for the administration of checkpoint modifiers are urgently needed. In this issue of EMBO Molecular Medicine, Aznar et al present the already approved yellow fever vaccine 17D as an oncolytic agent for tumour immunoactivation. In tumour‐bearing mice, they demonstrated a convincing synergy of the vaccine with CD137 agonistic antibodies resulting in significantly improved survival. Abstract : In this Issue of EMBO Molecular Medicine, Aznar et al demonstrate the therapeutic potential of the already approved yellow fever vaccine 17D for viro‐immunotherapy of cancer.